Particularities social-psychological adaptation subdivision commanders of the Interior Troops to independent professional activity - Lipatov, І. І. (Honor and Law, 2019)
Particularities social-psychological adaptation subdivision commanders of the Interior Troops to independent professional activity are defined. Recommendations on psychological accompaniment of the adapting the phyche commander subdivisions to independent professional activityare motivations.